Comunidade(s) Hip-Hop: a potência da quebra e a precariedade de corpos políticos - Magalhães, Camilla Millan Coelho de (2024)
What are the political strategies for Hip-Hop, as a community, to keep moving? This is one of the main questions of this dissertation, which aims to analyze how, over the decades, political destabilization and strategies occur so that the Hip-Hop community remains alive and powerful. Based on the understanding of corpomídia (Katz; Greiner), we understand the body of the breaker as the subject of important political demands and the center of a communication network that supports sociability and resistance. When reflecting on the movements of the Hip-Hop community, the proposal is to conduct the research in three stages: the historical recovery that made it possible to bring together several people who act socially based on Hip-Hop (and breaking); the theories and authors that help to think about political destabilization and bodily strategies to keep moving; and the association of personal experiences and studies into the possible paths of Hip-Hop. The corpus will consist of reports about my participation in dance championships, as well as interviews with dancers and an analysis of narratives around the changes in Hip-Hop culture. Publications on social networks, reports and interviews in the media were consulted, in addition to academic research, such as Teatro Hip-Hop (Estrela D’Alva), Necropolítica (Achille Mbembe), Homo Ludens (Johan Huizinga) and Barulho de Preto (Tricia Rose). Among the various aspects that will be addressed in the research are political changes, the aesthetic singularities of dance in Brazil (such as bridges with capoeira) and media coverage as a construction process that changes the political image of breaking. As a result, the research aims to highlight the powers of the body and the Hip-Hop culture, contributing to the field of dance studies in Brazil and highlighting the media’s role in transforming the way breaking is seen nationally